A new musculoskeletal ultrasound scoring system (US10) of the hands and wrist joints for evaluation of early rheumatoid arthritis patients - Luz,Karine R. (2016)
ABSTRACT Objective: To propose a novel ultrasound scoring system for hand and wrist joints (US10) for evaluation of patients with early rheumatoid arthritis (RA) and to correlate the US10 with clinical, laboratory and functional variables. Methods: Forty-eight early RA patients underwent clinical and laboratory evaluations as well as blinded ultrasound (US) examinations at baseline, three, six and 12 months. The proposed US10 system involved the assessment of the wrist, second and third metacarpophalangeal and proximal interphalangeal joints. The score consisted of inflammation parameters (synovial proliferation [SP], power Doppler [PD] and tenosynovitis [TN]) and joint damage parameters (bone erosion [BE] and cartilage damage [CD]). SP, PD, BE and CD were scored qualitatively (0–1) and semi-quantitatively (grades 0–3). Tenosynovitis was scored as presence/absence. The evaluation also involved the 28-Joint Disease Activity Score (DAS28), Health Assessment Questionnaire (HAQ) and C-reactive protein level (CRP). Results: Mean duration of symptoms was 7.58 ± 3.59 months. Significant correlations (p < 0.05) were found between inflammation parameters and CRP at baseline and between the changes in these variables throughout the study. Significant correlations (p < 0.05) were found between DAS28 score and both PD and TN at baseline and between the changes in DAS28 score and both SP and TN throughout the follow up. Moreover, significant correlations were found between the changes in inflammation parameter scores and HAQ score throughout the follow up. Conclusion: The proposed US10 scoring system proved to be a useful tool for monitoring inflammation and joint damage in early RA patients, demonstrating significant correlations with longitudinal changes in disease activity and functional status.